(untitled) (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDIES AND EDUCATION, 2026)
This paper examines the dual impact of artificial intelligence on contemporary education systems, investigating whether AI functions as a genuine catalyst for pedagogical development or as a mechanism that leads students toward cognitive passivity and intellectual dependence. According to research, adaptive AI systems are shown to construct personalised learning trajectories for individual students, reduce teachers’ administrative workloads by an average of 40 percent, and raise measurable student engagement by 25 percent. In Uzbekistan specifically, AI-enabled distance learning platforms have increased rural student retention by 28 percent, providing a powerful equity argument for accelerated adoption. At the same time, the data document serious deterioration: independent writing quality has declined by 18 percent among AI-exposed cohorts, plagiarism has surged 62 percent globally and 133 percent at Uzbek urban universities, and unaided recall performance among heavy AI users has dropped 15 percent.